1977
DOI: 10.1037/0022-0663.69.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual model for nonintellectual behavior and its relationship to early reading achievement.

Abstract: This article develops a rationale for a three-dimensional model of nonintellectual behavior of children and supports the rationale with a review of relevant theoretical and empirical work. Dimensions derived from a cluster analysis of the Pupil Behavior Rating Scale support the conceptual model by defining an adaptation and an interpersonal and an intrapersonal dimension. The adaptation and intrapersonal dimensions made important contributions to both first-and second-grade reading performance even when the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…Also, in Kellam et al (1975), the associations between each of six diverse behavioral items and either concurrent or subsequent achievement status were of nearly the same magnitude (see Tables 6 and 8; see also Stott, 1981, for similar findings). In addition, Lambert and Nicoll (1977) found that internalizing rather than externalizing ratings made independent predictions of later reading scores.…”
Section: Prospective Longitudinal Investigationsmentioning
confidence: 96%
“…Also, in Kellam et al (1975), the associations between each of six diverse behavioral items and either concurrent or subsequent achievement status were of nearly the same magnitude (see Tables 6 and 8; see also Stott, 1981, for similar findings). In addition, Lambert and Nicoll (1977) found that internalizing rather than externalizing ratings made independent predictions of later reading scores.…”
Section: Prospective Longitudinal Investigationsmentioning
confidence: 96%
“…1-19 Both cross-sectional and longitudinal studies have found that children who experience mental health problems are more likely to have unfavorable educational outcomes, including poor grades, 1-4,7,10,13-15,17,19 delays in reading, 5,6,18 grade repetition, 2,5 school drop-out ideation, 2 and lower educational attainment than their peers without mental health problems. 9,11,12 To provide just one example, a recent national study of more than 11,000 students in Chile found that mental health in first grade, as assessed with brief standardized teacher and parent screens, was one of the strongest predictors of performance on national achievement tests of language, mathematics, and science three years later.…”
Section: Introductionmentioning
confidence: 99%
“…16,23 However, the inclusion of mental health programs in schools is not yet mainstream, possibly because the empirical evidence supporting their effectiveness is limited. Research studies supporting the link between mental health and academic performance have used relatively small samples, 15,18 lacked prospective data, 11,17-19 used only a single measure of mental health, 17,18 and/or relied on self-report data of academic functioning. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Scores on the two instruments were strongly correlated (r = .87, p < .01), and sensitivity (.94) and specificity (.88) indicate the SCSQ can efficiently detect students with social challenges in need of a formal evaluation. KEYWORDS Asperger's Disorder, screening questionnaire, social challenges, Autism Spectrum Disorder, elementary school A substantial literature exists to indicate that social challenges in elementary school students are associated with limited academic performance (DiPerna & Elliott, 1999;Feshbach & Feshbach, 1987;Green, Forehand, Beck, & Vosk, 1980;Gresham & Elliott, 1990;Lambert & Nicoll, 1977;Wentzel, 1991Wentzel, , 1993. In addition to the effects on academic performance, subtle social challenges can be an indicator that social demands are exceeding the skills of the individual, which may suggest mild forms of Autism Spectrum Disorder (ASD) or another psychiatric condition.…”
Section: Schools Regularly Screen Students For Hearing and Vision Impmentioning
confidence: 97%